Validation of a new smart textiles biotechnology for heart rate variability monitoring in sheep - Turini, Luca; Bonelli, Francesca; Lanatà, Antonio; Vitale, Valentina; Nocera, Irene; Sgorbini, Micaela; Mele, Marcello (Frontiers in Veterinary Science, 2022)
Robust Animal-Based Measures (ABMs) are fundamental in order to assess animal welfare, however in semi-extensive sheep farming systems is not easy to collect ABMs measure without induce additional stress to animals. Heart rate variability (HRV) is a non-invasive technique of assessing stress levels related to animal welfare. It is considered a sensitive indicator of the functional regulatory characteristics of the autonomic nervous system. Several studies investigated the use of HRV for welfare assessing in dairy cows while research in sheep is scarce. Moreover, assessing HRV in small ruminants at pasture is critical because the lack of a solution adoptable on field conditions. The aim of this study was to evaluate if a smart textiles technology is comparable to a Standard base-apex electrocardiogram (ECG) for measuring HRV in small ruminants. Eight healthy Massese dairy sheep were recruited. Standard base-apex ECG and smart textiles technology (Smartex ECG) were simultaneously acquired for 5 minutes in the standing, unsedated, unclipped sheep. The ECG tracings were recorded when animals were standing quietly. The Bland-Altman test and the linear regression analysis were applied after parameter extraction in time, frequency, and nonlinear methods to compare Smartex against standard base-apex ECG systems. The Bland-Altman test was applied to all HRV extracted parameters (Mean RR, pNN50, RMSSD, LF/HF, SampEn, SD1, SD2, stdRR) to evaluate the agreement between the two different instruments and a linear regression analysis was performed to evaluate the relationship between the two methods. The smart textiles biotechnology was simply to wear and to clean. It can be worn without using glue and without shaving the sheep’s wool, limiting animal handling and stress. Bland Altman test reported a robust agreement between the two systems. In fact, the regression analysis of HRV parameters showed that half of the parameters recorded had an R2 coefficient greater than 0.75. Results also showed a very small reproducibility coefficient that indicated that two methods were really close to each other. Smartex textiles technology can be used for HRV evaluation in sheep species as a potential ABM for animal welfare assessment.